A Rare Case of a Translocation-Associated Perivascular Epithelioid Cell Neoplasm (PEComa) - Kimberly Pereira; Arati A. Inamdar; Aditi Zaveri; Jonathan E. Teitelbaum; Wendy Shertz; Kenneth Belitsis (Hindawi Limited, 2022)
A perivascular epithelioid cell tumor (PEComa) is a rare mesenchymal neoplasm composed of perivascular epithelioid cells with distinctive histologic, immunohistochemical, and genetic features. PEComas arising from various anatomical sites have been reported, but gastrointestinal PEComas are extremely rare entities. Here, we discuss the clinical and pathological features of a gastrointestinal PEComa with a transcription factor E3 (TFE3) translocation in a 17-year old adolescent male with a clinical presentation of abdominal pain and gastrointestinal bleeding. Our case report provides insight into this rare entity as well as discusses the pathophysiological aspects of TFE3-SFPQ-associated GI PEComas and their management.